2013
DOI: 10.1097/iae.0b013e3182657fff
|View full text |Cite
|
Sign up to set email alerts
|

Retinal Pigment Epithelial Atrophy in Patients With Exudative Age-Related Macular Degeneration Undergoing Anti–vascular Endothelial Growth Factor Therapy

Abstract: Atrophy was frequently observed in patients with age-related macular degeneration and choroidal neovascular membranes undergoing anti-vascular endothelial growth factor therapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
64
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 81 publications
(67 citation statements)
references
References 21 publications
2
64
1
Order By: Relevance
“…In eyes with neovascular AMD undergoing multiple anti-VEGF injections, Lois et al, [40] reported progression of RPE atrophy in approximately 60% of eyes. Moreover, the number of anti-VEGF injections was significantly associated with the progression of atrophy with each additional anti-VEGF injection increasing the odds of developing atrophy by a factor of 1.35.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In eyes with neovascular AMD undergoing multiple anti-VEGF injections, Lois et al, [40] reported progression of RPE atrophy in approximately 60% of eyes. Moreover, the number of anti-VEGF injections was significantly associated with the progression of atrophy with each additional anti-VEGF injection increasing the odds of developing atrophy by a factor of 1.35.…”
Section: Discussionmentioning
confidence: 99%
“…Also this aspect could be of particular relevance in clinics. Hence, there are emerging signals that anti-VEGF treatment can potentially increase development of RPE atrophy and even macular atrophy, leading to geographic atrophy (GA) [39, 40]. …”
Section: Discussionmentioning
confidence: 99%
“…37 Smaller-scale retrospective studies Lois et al detected RPE atrophy using short-wavelength AF and near-infrared AF (NIA) in a retrospective review of AMD patients with CNV treated with anti-VEGF. 38 They looked at atrophy at baseline and at progression of atrophy at follow-up of 72 eyes, treated with ranibizumab only, for a median of 16 months. They defined atrophy at baseline as a reduced signal in both AF and NIA of 40.05 mm2 in the absence of haemorrhage, exudates, or blockage of the AF/NIA signal related to the CNV when this was subretinal.…”
Section: Eyementioning
confidence: 99%
“…The exacerbation of RPE and choroidal atrophy by anti-VEGF theraphy in neovascular AMD has become a current topic [6,[9][10][11][12][13]. However, there is a lack of literature about retinal layers and anti-VEGF theraphy.…”
Section: Discussionmentioning
confidence: 99%
“…Besides, we know that VEGF inhibition also leads to nonperfusion of vessels in the choroid plexus [7], afterwards choriocapillaries and RPE degeneration occurs [8]. A great number of studies investigated the association between anti-VEGF treatment and RPE-choroidal atrophy by using fundus autofluorescence (FAF) or near-infrared autofluorescence, fluorescein angiogram and/or optical coherence tomography (OCT) imagings [6,[9][10][11][12][13][14][15][16]. However, there is limited study in the literature looking at the difference in retinal layers thicknesses in neovascular and nonneovascular AMD patients in order to determine the plausible effect of anti-VEGF treatment [17][18][19].…”
Section: Introductionmentioning
confidence: 99%